A rare case of adrenal hemangioma: A case report (Indian Journal of Case Reports, 2024)
Adrenal hemangiomas are rare benign tumors arising from the endothelial cells lining the blood vessels, which are made up of angioblastic cells. They are usually identified incidentally on radiographic imaging and post-operative histopathology is usually the definitive diagnosis. Computed tomography and magnetic resonance imaging help in the detection of silent adrenal lesions. We present a case and outline the diagnostic work-up and treatment of incidentally detected adrenal hemangioma in a 66-year-old woman.